New Developments in Galician Linguistics: An Introduction - Xosé Luís Regueira; Elisa Fernández Rei (Languages)
Minoritized languages that have recently been standardized exhibit distinct characteristics that shape the ideologies and social and cultural dynamics associated with them [...]